A comprehensive review of the antibacterial activity of dimethylaminohexadecyl methacrylate (DMAHDM) and its influence on mechanical properties of resin-based dental materials - Francisca Jennifer Duarte de Oliveira; Paulo Sérgio Ferreira da Silva Filho; Moan Jéfter Fernandes Costa; Marília Regalado Galvão Rabelo Caldas; Boniek Castillo Dutra Borges; Diana Ferreira Gadelha de Araújo (Elsevier, 2021)
The repetitive restorative cycle should be avoided, aiming at the smallest number of restorations' replacements to ensure greater tooth longevity. Antibacterial materials associated with the control of caries etiological factors can help improve restoration's durability. This review aimed to analyze the results of in vitro studies that added Dimethylaminohexadecyl methacrylate (DMAHDM), an antibacterial monomer, to restorative materials. The PubMed, SCOPUS, Web of Science, and Biblioteca Virtual em Saúde databases were screened for studies published between 2015 and 2020. After full-text reading, 24 articles were included in the final sample. DMAHDM has demonstrated antibacterial efficacy against several bacteria related to dental caries and periodontal diseases, causing a transition in the biofilm balance without inducing resistance. When DMAHDM was included in acrylic resin, the material cytotoxicity increased, and changes in mechanical properties were observed. In contrast, resin composites had their mechanical properties maintained in most studies; however, toxicity was not examined. The association between DMAHDM and 2-methacryloyloxyethyl phosphorylcholine or silver nanoparticles improved the antibacterial effect. Besides, the association with nanoparticles of amorphous calcium phosphate or nanoparticles of calcium fluoride can provide remineralization capacity. There is a lack of information on the cytotoxicity and bacteria resistance induction, and further studies are needed to address this.